Quality of Life in and After Spinal Cord Injury Rehabilitation: A Longitudinal Multicenter Study - Lude, P. (Top Spinal Cord Inj Rehabil, 2014)
PURPOSE: To investigate the changes in quality of life (QOL) in persons with spinal cord injury (SCI) and their close persons during the first 2 years post injury. METHOD: Longitudinal multiple sample multiple wave panel design. Data included 292 patients recruited from Austrian British German Irish and Swiss specialist SCI rehabilitation centers and 55 of their close persons. Questionnaire booklets were administered at 6 weeks 12 weeks 1 year and 2 years after injury to both samples. RESULTS: Study 1 investigated the WHOQOL-BREF domains in individuals with SCI and found differences mostly in the physical domain indicating that QOL increases for persons with SCI from onset. An effect of the culture was observed in the psychological and environmental domains with higher QOL scores in the German-speaking sample. Study 2 compared individuals with SCI to their close persons and found differences in the physical environmental and social domains over time. The scores on the psychological dimension did not significantly differ between the persons with SCI and their close persons over time. CONCLUSION: QOL measured by the WHOQOL-BREF shows that QOL changes during rehabilitation and after discharge. Apart from the physical dimension the persons with SCI and their close persons seem to experience a similar change in QOL. Further longitudinal research is suggested to clarify the mutual adjustment process of people with SCI and their close persons and to explore cultural differences in QOL between English-and German-speaking countries.